Grazing Cover Crops Improved Soil Health in Dryland Cropping Systems - Augustine K. Obour; John D. Holman; Logan M. Simon; Sandra K. Johnson (Kansas Agricultural Experiment Station Research Reports, 2023)
Integrating cover crops (CCs) in dryland crop production in the semiarid central Great Plains (CGP) can provide several ecosystem benefits. However, CC adoption has been slow in the CGP because CCs utilize water that otherwise would be available for the subsequent cash crop. Grazing CCs can provide economic benefits to offset revenue loss associated with decreased crop yields when CCs are grown ahead of a cash crop. Field experiments were conducted from 2015 through 2022 to quantify effects of grazing CCs on soil bulk density, aggregate stability, and chemical properties across western Kansas. At the Kansas State University HB Ranch near Brownell, KS, grazed CCs were compared to non-grazed CCs and fallow in a wheat-sorghum-fallow rotation. The on-farm study evaluated CCs grazed with yearlings or cow-calf pairs compared to non-grazed CCs across seven site-years on producer fields in western Kansas (Alexander and Hays) and central Kansas (Marquette). Averaged across 8 years, hayed and grazed CCs removed 71% and 40%, respectively, of available CC biomass at Brownell. Across on-farm sites, CC residue after grazing averaged 2210 lb/a compared to 3475 lb/a for the non-grazed CCs, representing a 36% decrease in CC biomass with grazing. Grazing days across farms ranged from 25 to 54 days with average daily gain of 1.2 to 3.11 lb/d. Soil characteristics including bulk density, penetration resistance, aggregate size distribution, and mean weight diameter (MWD) of water stable aggregates were not different between grazed and non-grazed CCs. Cover crops tended to increase soil organic carbon (SOC) concentration compared to fallow or initial SOC levels in some site-years. For example, SOC measured at the surface 0- to 2-inch depth near Hays, KS, in spring 2019 was 1.4%, which was significantly less than the 2.1% SOC measured in 2021 after two cycles of grazing CCs at this location. Penetration resistance measured after grazing in 2021 averaged 52.2 and 49.3 psi for the grazed and non-grazed CCs at Marquette, KS. Similarly, penetration resistance averaged 75.4 psi with grazed and non-grazed CCs at Alexander, KS. The penetration resistance measured across locations and CC management strategies was below the threshold of 300 psi that will limit root growth. Based on findings of this study, integrating CCs with livestock can be a strategy for producers to balance profitability and soil health in dryland crop production in western Kansas.
Keywords: cover crops; grazing; soil health